As «Leis Jacobinas». Estudo e transcrição - Margarida Garcez Ventura (Medievalista)
As in another realms of Christianity, also the portuguese king, using both the theological reasons as the roman law, considered his right and duty to exercise jurisdiction over many cases that the clergy had as exclusively theirs. Here is a brief comment on the so called “Leis Jacobinas” (Nov. 1418-Dec. 1419), simultaneously trigger and witness of the controversy between the Church and the royal power in the late Middle Age. We also publish a new reading on one of the transcriptions of these laws.